PENGEMBANGAN MEDIA KOMIK DIGITAL BERBASIS CANVA PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS III SEKOLAH DASAR - Hasanah, Nur; Hamimah; Safitri, Serly; Shilfia Iraqi, Hana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research addressed low motivation and engagement among third-grade elementary students in learning IPAS, particularly landform material, as teachers had not optimally used digital media. This R&D study, using the ADDIE model (Analyze, Design, Development, Implementation), developed a Canva-based digital comic media for IPAS learning with the Problem Based Learning (PBL) model. Trials were conducted at SDN 03, 15, and 06 Pulai Anak Air. Validity data came from expert questionnaires; practicality data came from teacher and student responses, analyzed descriptively. The media achieved 94.58 percent average validity (very valid) and practicality of 97.22-100 percent from teachers and 94.02-97.39 percent from students (very practical). The media is thus valid and practical for IPAS learning on landform material.